THE CURRENT STATE OF SEED PRODUCTION OF VEGETABLES AND GOURDS IN RUSSIAN FEDERATION; NATIONAL FOOD SAFETY - S. M. Sirota; E. G. Kozar; Ju. N. Nikolaev (Овощи России, 2017)
The current state of seed market of vegetable and gourds in Russian Federation in the frame of national food safety program is given in the article. Russia as a country with well-developed  seed production  in the last century has now  ceded  its  position,  and according  to  last experts’ association estimations the 80%  of  required volume of seeds of vegetables and gourds, amounting from 8 to 12 thousand per year is imported.  Not  less than 15 thousands  of  hectares  are  needed  to  be  necessary  for demand  of  Russian seed  production  sector,  however, presently only 2 thousands of hectares is a total certified land used for seed production.  Moreover, the seed production sector of some countries that export seeds rises becoming a profitable branch of agriculture, and providing local employment. The lack of competitiveness in Russia causes that many foreign companies increase annually purchasing prices for seeds and their production services. Therefore, now the total volume of seeds imported  in  Russian Federation has nearly been  twice less for the last years than in 2012, but in currency earnings in exporting countries the insignificant changes can be seen, where deviation is only 19-25%  from  average annual value, that means 1675 thousand dollars per year. Besides, for the Russian budget in the ruble currency the total cost of imported seeds has become 2.5 times more expensive since 2012, but the increase of combined cost of  marketable  vegetables  has been  over  2.7  billion  of rubles.  The  main  idea  that  the  seed  production  is  a process requiring the participation of breeders, seed producers and seed companies is main factor to succeed in recovering seed production sector. Exception of any participant or ignoring his interests may destroy all process. For instance, there is a chronic problem of plagiarism and royalty nonpayment causes the break between the business and breeder, affecting on the final result. It is evident  that  the development  of  National Associations for Professional Unions of breeders, seed growers and businessmen with active participation of the governments in building regulatory and legal base, rules and mechanisms of relationships for all partners in seed market enables to develop the effective and stable national system of seed production.